PRESERVASI BUDAYA OTOMOTIF MELALUI MUSEUM SEJARAH DI KEMAYORAN, JAKARTA - Putra, Samuel Losan; Hadiwono, Alvin (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
The Kemayoran area has a unique history and culture. The automotive culture, with its history in Kemayoran, is a hidden aspect that has left a significant impression on automotive enthusiasts in this century, which is gradually being forgotten as interest in automotive activities among the residents of Kemayoran declines. This journal aims to explore how architectural science can be used to preserve and potentially revive automotive culture and interest in Kemayoran. With the understanding of the phrase "Placeless Place," it can be seen that Kemayoran is starting to lose its significance as an ideal area for automotive-themed activities. By employing placemaking methods and examining the history of the Kemayoran area while focusing on the present, a review of how to preserve historical elements through architecture emerges. Through these methods and in-depth studies, iconic points of Kemayoran automotive history and ideal forms of historical preservation were obtained. An architectural design in the form of a historical museum building with complementary facilities in the form of entertainment and commercial, can help maintain and give birth to automotive interests that are starting to fade for residents of the Kemayoran area. The history of Kemayoran automotive culture can be preserved through architecture. Keywords:  automotive culture; history museum; interest; placeless place; preservation Abstrak Wilayah Kemayoran memiliki berbagai sejarah dan budaya yang cukup unik. Budaya otomotif dengan sejarahnya di daerah Kemayoran merupakan sebuah aspek tersembunyi yang cukup berkesan abad ini bagi para penggemar automotif, yang secara perlahan dilupakan dengan berkurangnya minat kegiatan otomotif penduduk Kemayoran. Jurnal ini bertujuan untuk meneliti cara ilmu arsitektur bisa digunakan untuk menjaga dan kemungkinan membangkitkan budaya dan minat otomotif di Kemayoran. Dengan pemahaman kalimat “Placeless Place”, dapat dilihat bahwa Kemayoran mulai kehilangan makna sebagai kawasan ideal untuk kegiatan bertema otomotif. Dengan metode placemaking, melihat sejarah kawasan Kemayoran dan memfokuskan pada masa sekarang, maka muncul sebuah ulasan cara preservasi bagian sejarah melalui arsitektur. Melalui metode dan pendalaman tersebut, dipetik poin-poin ikonis sejarah otomotif kemayoran dan bentuk preservasi sejarah yang ideal. Sebuah perancangan arsitektur berupa bangunan fungsi museum sejarah dengan fasilitas pelengkap berupa hiburan dan komersil, bisa membantu menjaga dan melahirkan minat otomotif yang mulai pudar bagi para penduduk wilayah Kemayoran. Sejarah budaya otomotif Kemayoran dapat dipreservasi melalui arsitektur.